Study on Synthesis of 1,8-Dioxooctahydroxanthene by Silica Supported Orthophosphoric Acid (H\(_3\)PO\(_4\)•SiO\(_2\)) - Patil, Rahul Shankarrao; Mali, Ankush V.; Burungale, Shivaji H. (Challenges and Advances in Chemical Science Vol. 5, 2021)
Reusability of heterogeneous catalyst provide wide advantages over homogenous catalyst so that we have developed a novel method of preparation of xanthenediones by condensing aldehyde and dimedone in 2:1 proportion by using silica supported orthophosphoric acid (H3PO4.SiO2) as a catalyst. The developed protocol was scalable, simple and high sensitive to the various substituted aldehydes.